Traumatic damage to the mitral valve during percutaneous balloon valvotomy for critical aortic stenosis - Brierley, J (1998)
Percutaneous balloon valvuloplasty is now a widely accepted alternative to surgical valvotomy for patients with congenital aortic valve stenosis. Mitral valve anomalies are well known to coexist and influence the prognosis from all palliative procedures. Two cases of mitral valve injury occurring during balloon aortic valvuloplasty are reported, one an 11 month old boy, the other a 2 day old baby boy. Both cases were characterised by an unusually posterior position of the guidewire, over which the balloon was deployed. The wire, and hence the balloon, may have been placed through the tension apparatus of the mitral valve with subsequent damage to its free edge on inflation. This is at least conceptually more likely to occur if the orifice of the valve is posterior, if there is a small left ventricular cavity, or if the mitral valve itself is abnormal—features present in both cases. Possible strategies for decreasing the incidence of such damage are considered.   Keywords: critical aortic stenosis;  mitral valve damage;  percutaneous balloon valvotomy